Study Interest Analysis on Indonesian Language Subjects - Muhammad Bakri; Yuni J Salamangi; Fien Pongpalilu (STAI Hubbulwathan Duri, 2022)
This study aims to analyze interests in the Indonesian Language subject. This study uses a descriptive analysis method using a qualitative approach and tests the hypothesis using the interpretation of the percentage value. This study found that interest in learning Indonesian increased significantly; this is evidenced by the claim that students have in learning Indonesian, both individually and in groups. Alternatively, in other words, taking part in Indonesian language exercises that are beneficial for students in Indonesian subjects—increased because it is influenced by factors of motivation and the state of the school environment, and the role of the teacher.